Preparation and characterization of co-doped (Ce 0.80La 0.15Al 0.05O 1.90) and multiple-doped (Ce 0.80Sm 0.10Gd 0.05Al 0.05O 1.90 and Ce 0.80Gd 0.10Sm 0.05Al 0.05O 1.90) ceria - Singh N.; Singh N.K.; Parkash O.; Kumar D. (My University, 2025)
Attempts have been made to synthesize a few compositions Ce 0.80La 0.15Al 0.05O 1.90, Ce 0.80Sm 0.10Gd 0.05Al 0.05O 1.90, and Ce 0.80Gd 0.10Sm 0.05Al 0.05O 1.90 by citrate-nitrate auto-combustion method. The aim of the present investigation was to study the effect of co-doping and multiple doping on the ionic conductivity of CeO 2 for its use as solid electrolyte in intermediate temperature solid oxide fuel cells. XRD patterns showed that all the samples have fluorite-type crystal structure similar to undoped ceria. Microstructures of thermally etched samples have been studied by scanning electron microscopy. Contributions of grains σ g and grain boundaries σ gb to the total conductivity σ T, have been determined using impedance analysis. Impedance measurements were made in the frequency range 1 Hz-1 MHz and temperature range 250-500 °C. Our experimental results show that multiple doping is more effective than co-doping for improving the oxide ion conductivity of ceria in the materials investigated in the present study. © 2011 Springer-Verlag.